A intertextualidade camoniana em "...Onde Vaz, Luís?" (1983) de Jaime Gralheiro ou Luís Vaz de Camões revisitado no teatro português contemporâneo (Studia Iberystyczne, 2019)
Camoenian Intertextuality in "...Onde Vaz, Luís?" (1980) by Jaime Gralheiro or Luís Vaz de Camões Revisited in the Contemporary Portuguese TheaterThe objective of the article is a comparison between Os Lusíadas/The Lusiads (1572) by Luís Vaz de Camões and ...Onde Vaz, Luís (1983) by Jaime Gralheiro, showing the processes of narrative incorporation of an epic pattern into the dramatic hypertext, made through a “mosaic of quotations”. The discussion attends to the generic transformation, a very productive one in terms of aesthetics and ideology, with visible traits of parody, disguise, pastiche, narrative transposition of more than one unique text but many of them by various Portuguese authors of the 16th century (including Fernão Mendes Pinto, António Ferreira, Pedro de Andrade Caminha, Damião de Góis, Gil Vicente) ment for a jocular dramatic piece, both tragic and grotesque, conceived out of social criticism and according to a Brechtean ideological character. The article shows a sample of multiple relations between the primary hypotext and the texts derivated out of it, confirming the present paper’s aim in many works of Portuguese literature writers, of prose and theater writings. The heroic hypotext vs. the hypertexts are unfolded in dramatic and novelesque post-modern refabulations (José Saramago included!). Another study of the imaginary makes the realm of revisiting the Portuguese literature is possible in relation to contemporary history and human existence, with space-and-time frontiers and literary genres extinguished in the “intertextual lottery” of Camões and his metamorfoses with regard to fictional authors and protagonists. A diagnosis of hic et nunc (just now!) is being produced in a methodologically consistent way according to the classics of intertextuality focused on dramatic and romanesque writings in Portugal in the decline of the former century. The Carnations’ Revolution in the background and the revolutionary democratic aftermath accompanying the undertaken analytic process.